2017
DOI: 10.1007/s00270-017-1736-8
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Chemoembolization Monotherapy Versus Combined Transarterial Chemoembolization–Microwave Ablation Therapy for Hepatocellular Carcinoma Tumors ≤5 cm: A Propensity Analysis at a Single Center

Abstract: Compared with TACE, TACE-MWA leads to better responses for HCC tumors ≤5 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 22 publications
2
40
0
Order By: Relevance
“…ALB, Albumin; AST, Aspartate aminotransferase; ALT, Alanine aminotransferase; TBIL, Total bilirubin feasibility of TACE combined with MWA [21,22]. A retrospective study of 244 HCC patients highlighted that the tumor response (CR + PR + SD) rates at 6 months was 92.1% in the TACE-MWA group compared with 46.3% noted in the conventional TACE (P < 0.001), and they concluded that patients with HCC tumors equal to or smaller than 5 cm in diameter (≤5 cm) exhibited a better response to combined treatment than that noted for TACE alone [23]. Additionally, the 1-, 3and 5-year OS rates were significantly higher in the combination therapy group than those in the TACE alone group (p < 0.001) [24].…”
Section: Discussionmentioning
confidence: 99%
“…ALB, Albumin; AST, Aspartate aminotransferase; ALT, Alanine aminotransferase; TBIL, Total bilirubin feasibility of TACE combined with MWA [21,22]. A retrospective study of 244 HCC patients highlighted that the tumor response (CR + PR + SD) rates at 6 months was 92.1% in the TACE-MWA group compared with 46.3% noted in the conventional TACE (P < 0.001), and they concluded that patients with HCC tumors equal to or smaller than 5 cm in diameter (≤5 cm) exhibited a better response to combined treatment than that noted for TACE alone [23]. Additionally, the 1-, 3and 5-year OS rates were significantly higher in the combination therapy group than those in the TACE alone group (p < 0.001) [24].…”
Section: Discussionmentioning
confidence: 99%
“…The propensity score model was determined by previous studies (8,11), the independent variables used in the matching included gender, age, alpha-fetoprotein (AFP) level, Child-Pugh score, alanine aminotransferase (ALT), tumor size and tumor number. Propensity score matching was performed using optimal matching method at the ratio of 1:2 (9).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, two retrospective studies demonstrated the superior treatment effectiveness of the TACE-MWA combination therapy compared with the TACE monotherapy for specific HCC patients (7,8). However, their studies did not specify the BCLC stage and included HCC patients at BCLC stages A, B, and C. Our study focused mainly on BCLC stage B patients with tumor size ≤7 cm and tumor number ≤5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, TACE, despite of being recommended for intermediatestage HCC in the guidelines, has also been a valid option for patient ineligible for curative treatment with early-stage HCC in clinical practice. 25,26 However, there is a paucity of study comparing therapeutic effectiveness between MWA and TACE for HCC in early-stage. Hence, to present more clinical reference of the treatment allocation for early-stage HCC, we conducted this retrospective study.…”
Section: Discussionmentioning
confidence: 99%